Boosting customers’ impulsive buying tendency in live-streaming commerce: the role of customer engagement and deal proneness - Luo, Xi; Cheah, Jun-Hwa; Hollebeek, Linda D.; Lim, Xin-Jean (Elsevier, 2024)
With the ever-growing popularity of live-streaming commerce, it is crucial for marketers to understand how live-streaming contributes to sales. While prior studies mainly focused on customer motivations for using live-streaming commerce, few studies, to date, elucidate consumers' decision-making process in this context. Addressing this gap, we adopt the Elaboration Likelihood Model (ELM) of persuasion to examine how live-streaming influences customers’ engagement and impulse buying behavior, as moderated by their deal proneness. To explore these issues, we analyzed data collected from 735 Millennials in China using partial least squares structural equation modeling (PLS-SEM). The findings show that factors characterizing the ELM-informed central (i.e., product information quality, streamer interaction quality, and streamer credibility) and peripheral (i.e., review consistency) routes exert positive effects on customer engagement and impulse buying. Moreover, deal proneness was found to moderate the relationship between engagement and impulse buying. The findings offer valuable insight for e-tailers seeking to encourage impulsive buying among millennial shoppers. Specifically, they highlight the role of central- and peripheral route factors in promoting customer engagement and impulsive buying, with the effect of customer engagement on impulsive buying being contingent on deal proneness-based differences among millennial shoppers.